ICT utilization in teaching-learning of mathematics: a call for proper integration and enhancing teachers –students’ performance in the developing countries - ODIRI E ONOSHAKPOKAIYE (The University of Kuningan, 2022)
The study looked at the ICT utilization in teaching-learning of mathematics: a call for proper integration and enhancing teachers–students’ performance in the developing countries. The importance of mathematics cannot be played down. Everyone uses it in their everyday activities. Mathematics has been seen as the basis for the economic, scientific and technological development of every nation. To sustain this importance, it becomes imperative to encourage students to study the subject and one way to do that is to effectively integrate the ICT into teaching the subject. The ICT is very essential in the study of mathematics because of its benefits. In integrating these ICT tools, there are problems encountered by the mathematics teachers which is require to be solved. The study reviewed the literature on the nature of mathematics, the vision of ICT, the nature of ICT, incorporation of ICT into teaching mathematics, problems of utilizing ICT in mathematics teaching-learning, the willingness of ICT use in Mathematics Education, ICT and its influence on mathematics teaching-learning, the benefits of applying ICT to Learning and Teaching Mathematics, Some ICT tools utilized for mathematics teaching, some recommendations were made by the researcher and forty-nine authors were reviewed to support the study.